Pengaruh Kualitas Audit, Tata Kelola Perusahaan, Tingkat Utang, dan Ukuran Perusahaan Terhadap Intergritas Laporan Keuangan - Thito Hermawan; Royhisar Martahan Simanungkalit (Economic Reviews Journal, 2024)
The purpose of this research is useful for empirically reviewing the impact of audit quality, corporate governance, leverage, and company size on the integrity of financial statements. There are independent variables including audit quality using the Big Four or Non-Big Four assessment, corporate governance used, namely independent commissioners from the percentage of how many independent commissioners and audit committees there are in an entity, the level of debt using the Debt to Asset Ratio, and company size using the natural logarithm of total assets and the dependent variable is the integrity of financial statements using Accounting Conservatism. The sample in the research is entities in the IDX 30 group listed on the IDX for the 2020-2022 period. This study obtained secondary data from the financial statements of 30 entities reduced through purposive sampling method resulting in 17 entities that met the research sample requirements, resulting in a total sample size of 51 data. This research method with descriptive statistical tests followed by classical assumption tests which include normality, multicollinearity, autocorrelation and heteroscedasticity. Furthermore, rise testing using regression equation analysis is continued by testing the hypothesis of how the independent variables affect the dependent. The test uses simultaneous test (F test), Coefficient of determination test and T-Statistic test (partial). Based on the findings of this study conducted by researchers, it was found that audit quality, corporate governance, and company size provide positive results that significantly affect the integrity of financial statements, and leverage has a negative impact that significantly affects the integrity of financial statements.